Resting Autonomic Function in Active and Insufficiently Active People Living with HIV - Quiles, Norberto; Garber, Carol; Ciccolo, Joseph (International Journal of Sports Medicine, 2018)
Autonomic dysfunction appears to be prevalent in people living with HIV/AIDS (PLWHA). However, there are limited data on the resting autonomic responses to exercise in active and insufficiently active PLWHA. We aimed to determine whether active PLWHA have better autonomic responses compared with insufficiently active PLWHA. Active PLWHA receiving anti-retroviral therapy (n=13) and insufficiently active PLWHA (n=10) were recruited. A 10-min recording of the supine electrocardiogram was taken. Resting heart rate variability was analyzed from this electrocardiogram. Parasympathetic modulation, as measured by high frequency power in normalized units, was greater in active PLWHA when compared to insufficiently active PLWHA (41.0±15.6 vs. 25.2±9.7; p<0.05). Sympathetic modulation as measured by low frequency power in normalized units was greater in insufficiently active PLWHA when compared to active PLWHA (55.6±15.8 vs 79.3±17.5; p<0.05). Sympathovagal balance as measured by low frequency/high frequency ratio was greater in insufficiently active PLWHA when compared to active PLWHA (3.4±1.8 vs 1.6±0.9; p<0.05), indicating greater parasympathetic dominance in the active group. In conclusion, PLWHA who regularly exercised demonstrated enhanced autonomic function compared with insufficiently active PLWHA. These results suggest that exercise is associated with enhanced autonomic function, and may improve cardiovascular risk.
Keywords: exercise; heart rate variability; chronic disease; cardiovascular disease risk; AIDS